Policy for the Treatment of Insulting and Sensitive Lexical Items in the Woordeboek van die Afrikaanse Taal - Harteveld, Pieter; van Niekerk, A.E. (Lexikos, 1995)
Outline of the policy for the treatment of insulting and sensitive lexical items in the Woordeboek van die Afrikaanse Taal: Common to all sensitive lexical items --- all simplexes, compounds and expressions are lemmatized --- all conform to the general usage criterion of the Bureau --- clear and correct labelling takes place, which also applies to insulting synonyms --- the metalanguage is neutral --- no collocations or editorial usage examples are given --- citations (where included) are chosen with care --- articles are checked by advisors to the Bureau A. Racist terms 1. Treatment in the WAT (a) Wholly racist lexical items --- for the definition, the item is referred to the most commonly used synonym; no racist synonyms are, however, given at neutral or racist lexical items --- no semantic oppositions are given --- no citations are given --- expressions are explained; no synonyms, antonyms, references and illustrative material are given with such expressions --- the same manner of treatment applies to racist expressions under neutral lemmas --- complete treatment takes place in electronic form (see 2 below) (b) Partially racist lexical items --- neutral semantic distinctions are treated in full --- racist semantic distinctions and expressions are treated as wholly racist lexical items 2. Treatment in the electronic manuscript --- references to or the noting of synonyms and semantic oppositions are given --- citations are given --- electronic manuscript is available on request B. Sexist terms and sensitive lexical items which indicate stigmatized sexual phenomena, practices and preferences among people --- the definition is given at the most commonly used neutral synonym --- references to or the noting of synonyms are given --- antonyms and formal references are given --- citations are given --- expressions are explained C. Sensitive lexical items which indicate stigmatized physical or mental conditions and phenomena among people --- treatment as in B above D. Sensitive lexical items within a social, political and religious structure --- treatment as in B above E. Obscene and vulgar lexical items, abusive language and swear-words --- treatment as in B above Keywords: policy, treatment, insulting lexical items, sensitive lexical items, dictionary, woordeboek van die afrikaanse taal, simplexes, compounds, expressions, general usage criterion, labelling, synonyms, metalanguage, collocations, editorial usage examples, citations, advisors, racist lexical items, neutral lemmas, electronic manuscript, references, semantic oppositions, sexist terms, stigmatized sexual phenomena, stigmatized physical conditions, stigmatized mental conditions, political items, religious items, obscenities, vulgarisms, abusive language, swear-words